Pengaruh Variasi Fraksi Volume Komposit Serat Sabut Kelapa Matrik Polyester Terhadap Kekuatan Tarik - Zarviansyah, Putra; Juanda, Juanda; Pranandita, Nanda (Jurnal Inovasi Teknologi Terapan, 2023)
In the era of the use of technology that is currently developing. Has a major impact on the use of fiber as a composite material. One of the widely used fibers is coconut coir. Coconut coir is a natural fiber material that can be an alternative choice in the manufacture of composites. The purpose of this study was to obtain optimal tensile test values of coco fiber composite materials with variations in volume fraction of 3%, 5% and 7% and fiber lengths of 10 mm, 15 mm and 20 mm. This study analyzes the effect of variations in the volume fraction and fiber length of coconut coir with a polyester matrix on tensile testing using the Taguchi method. This tensile test was carried out using the ASTM D638 standard with the hand lay-up method. Factors that affect the tensile strength of coco fiber are volume fraction and fiber length. The combination of levels of factors that produce the average value and variance of the tensile strength of coconut coir fiber, namely the volume fraction factor (B) level 1, namely the volume fraction of 3% with a value of 30.933 and the fiber length factor (A) level 2, namely the fiber length of 15 mm with the most optimum value of 29.633.